Resistence to Klitih Behavior Based on Character Education - Setiawan, Didy; Muhammad, Amin Rais; Na'imah, Na'imah (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2023)
This article examines the role of character education in addressing the issue of klitih behavior, which has recently become a trending topic on various social media platforms and has caused concern within the community. A descriptive qualitative approach is employed in this study, using a literature review as the research method, with data collection conducted through the 3M method: recording, analyzing, and integrating findings from previous studies that are relevant to the research theme. The results of this article's research indicate that klitih, as one form of delinquency among adolescents that has caused concern within the community, is influenced by several factors, including: lack of parental attention, family problems, negative environments and associations, the desire for recognition within a group/gang, insufficient knowledge of moral and religious values, and an already formed aggressive character in the child. Character education plays a crucial role in preventing and addressing this klitih behavior by shaping and instilling positive character values in children. Therefore, character education is considered a potential solution to address moral issues among teenagers/students.